Kelayakan Ekonomi Budidaya Nilam (Pogostemon cablin) di Desa Puundoho Kecamatan Pakue Utara Kabupaten Kolaka Utara - Syamsuri, Syamsuri; Alang, Hasria (Department of Agribusiness, Halu Oleo University, 2021)
Economic potential is the capacity of an area that contains potential resources, both natural resources and human resources, to be developed and become an opportunity in improving the community’s economy by looking at the real income of the people in that place. One way that can be done to improve the community’s economy is optimizing the superior plants in the area. Economic development can be done by maximizing the effect of commodities that already exist and cultivated for a long time. Puundoho Village is one of the villages with superior crops grown, namely Patchouli. Patchouli oil has high economic value because it contains compounds, terpenoids, phytosterols, flavonoids, organic acids, lignin, alkaloids, glycosides, alcohol, and aldehydes are used in the health and cosmetic fields. The purpose of the study was to see the feasibility of the economic potential of Patchouli (P. cablin) in Puundoho Village using Analisis Revenue Cost Ratio (R/C). The research was conducted from January to February 2021. The method used in this research is qualitative and quantitative. It was collecting data through observation and interviews. The results ratio showed 5,86, so it can be interpreted that Patchouli Industry is feasible to develop.